Factors affecting COVID-19 outcomes in Ireland: findings from a national database of 1,408,249 cases diagnosed between 2020 and 2022 - Shiraz Syed; Cecily Kelleher; Patricia Fitzpatrick (BMC Public Health)
Abstract Background Serious outcomes of COVID-19 may include admission to an intensive care unit (ICU) or death. Multiple risk factors exist which may contribute to these outcomes. The aim of the study, employing a large national dataset, was to assess roles of smoking, body mass index, metabolic and underlying clinical conditions in ICU admissions and death among those with COVID-19 in Ireland. Methods The analysis comprised all 1.4 million adult patients who tested positive with COVID-19 between April 2020 and December 2022. A pseudonymised dataset from the Central Statistics Office (CSO) was used; informed consent was waived by the National Health Research Consent Declaration Committee. Key variables above were used, employing both univariate and multivariate analysis. Outcomes were ICU admission and death with COVID-19. Results Mean age was 42 years (Standard Deviation (SD) 16.8) and 53% were males. Those admitted to hospital were older (59.2 (14.2)) than those who died (74.9 (12.0)). Increased odds ratios (95% CI) each significantly associated with ICU admission in multivariate models were, current/ex-smokers (2.4 (2.2–2.6)), males (1.8, (1.7–1.9)), and individuals with an underlying clinical condition (10.2 (7.9–13.2)). Odds of death were also significantly increased in presence of an underlying condition (186.129 (137.987-251.066)) but not when age was taken into account as an interaction term. Conclusion This comprehensive study confirmed international findings associated with poor outcomes in COVID-19. Whilst clinical indications for ICU admission and overall mortality may differ in hospitalised patients, the main drivers of mortality are age, underlying conditions and disease severity, irrespective of location.